REFLECTIONS OF JOHANNINE EPISTLES' CHRISTOLOGICAL HERESIES IN THE ACTIVITIES OF ANGLICAN FASTING AND PRAYING SOCIETY IN THE DIOCESE OF UGHELLI, DELTA STATE, NIGERIA (2014)
Christological heresies, which refer to the misconception of the divinity and humanity of Jesus that plagued the first century Johannine community, was overcome after three centuries of its emergence. These have resurfaced in Nigeria through the teachings of Evangelist Daniel Mimeyeraye of the Anglican Fasting and Praying Society (AFPS) in the Anglican Diocese of Ughelli. Previous studies on Christological heresies focused on heretics' background and the effects of their teachings on the Johannine community without reference to their resurgence in the contemporary Christian community, particularly the Anglican Diocese of Ughelli. This study, therefore, examined the manifestations of Christological heresies in the Johannine Epistles and related them to the teachings of Evangelist Daniel Mimeyeraye and the activities of AFPS with the aim of establishing their effects on interpersonal relationships in Ughelli Diocese. The study adopted Van Baalen's action and practice theory. Six hundred copies of a questionnaire were administered to 25 clergymen and 575 laity purposively selected from 17 of the 21 Archdeaconries in Ughelli Diocese where heretical teachings were prevalent. Indepth interviews were conducted with the founder of AFPS, Evangelist Mimeyeraye and six founding members. Church records were also consulted. Data were subjected to exegetical analysis (with reference to I Jn. 4:1-3, II Jn. vs 7-11, III Jn. vs 9-14) and percentages. Christological heresies in Johannine Epistles comprised Docetism (the teaching that Jesus was a spirit not a human entity), soteriological conflict (the belief that salvation comes through secret knowledge) and unethical behaviour (a sinful lifestyle). These teachings negated Christian belief in Jesus' humanity (II Jn. vs 7), divinity (I Jn. 2:22), exclusive salvation (Acts 4:12) and piety (I Jn. 3:6). These concepts divided the Johannine community, leaving believers confused about Christ. Evangelist Mimeyeraye's teachings were consistent with those of the heretics in Johannine epistles. Like the docetists, Mimeyeraye misconstrued Jn. 10:30 that Jesus is a spirit and not human. This is inconsistent with I Jn. 4:2-3, which agreed with Jesus' claim in Jn. 1:14. On soteriology, he misinterpreted Jn. 16:12-14 to mean that esoteric knowledge would lead to salvation for believers and their dead relatives who died without Christ. This teaching is contrary to Acts 4:12 which bestowed salvation on Jesus alone and Jn. 3:18 which condemned unbelievers. In spite of the wrong conception, 33.6% of the respondents subscribed to this teaching. Furthermore, he taught that unethical behaviour of AFPS members would not affect their salvation. This is against biblical teachings in Rom. 6:1-2, Heb. 12:14. However, 22.1% of the respondents agreed with Mimeyeraye's teaching. As in the Johannine community, Mimeyeraye's teaching divided Anglican Parishes in Ughelli Diocese and caused interpersonal clashes as recorded in the 1998 Ughelli diocesan synod report. Mimeyeraye's teachings, representing the ideology of the Anglican Fasting and Praying Society which were consistent with Christological heresies are at variance with Jesus' divinity, Christian salvation and ethical standards. Consequently, the church should institute a teaching against heresies and administer sound theological training to her ministers in order to stem the tide of wrong doctrine and interpersonal clashes.